Capacitively-coupled dual ring antennas for bolt loosening detection. (15th August 2022) - Jiang, Kang; Xie, Liyu; Xue, Songtao; Wan, Guochun
Highlights: A stacked-dual-ring-antenna sensor is proposed for the detection of bolt loosening. The nut rotation affects the coupling capacitance within the dual ring antennas. This device is suitable for in-service bolts and can be massively deployed. This proposed sensor has the advantages of no battery supply, wireless communication and coverage-defying. Abstract: This paper proposes a passive and wireless UHF (Ultra High Frequency, operating in 450–550 MHz) antenna sensor for bolt loosening detection. The novelty of this sensor is the introduction of nut's rotation angle as sensing variable, achieving the whole process of bolt status monitoring, and easy installation enabling the sensor to be applied in in-service bolt loosening monitoring. The sensor consists of two concentric rings, and the overall size is 116 mm × 92 mm × 2.4 mm. When the bolt is loose, the nut's rotation will change the coupling capacitance of the antenna and thus the resonant frequency. The electromagnetic performance of the sensor is simulated in HFSS and the quality factor calculated by HFSS is 52.87. Furthermore, the ability to characterize bolt's status was validated in the experiments. The results demonstrate that the resonant frequency increases linearly with the loosening of the bolt (the correlation coefficient is 0.9789) and the antenna's sensitivity is 2.95 MHz/degree.